Caracterización litológica y paleontológica del Cretáceo inferior en Cajamarca: Las formaciones Santa y Carhuáz - Lagos M y Cols., Alejandro (2019)
In this study, we analyzed the fossils and rocks of the formations Santa and Carhuaz of Cretaceous age found in the towns of San Marcos and Cajamarca determining its age and condition of their deposition. The determination of the relative heavy middle position (PMPR) of the sandstones of the fm. Carhuaz determined regional depositional characterization. It should be noted that both the fm. Santa as Carhuaz Miocene intrusive contact often behave as good host rocks for mineralization events, such as reservoir type Cu-Mo Porphyry El Galeno, located in the Department of Cajamarca. The fm. Santa, a name given by [1] of Cretaceous age, consists of an alternation of dark gray claystones and calcareous siltstones of marine transgressive character, lies in keeping on-shore beach sands of the fmcontinental. Chimú. According to [2] this machine exhibits regionally significant facies change, while in the northern limestone proportion is higher, more lutacea Cajamarca. In the towns of Matara- Namora and located in the San Marcos Quadrangle, gastropods were identified, which according to [3] are (Cassiope) neumayri (GAAS); paraglauconia strombiformis (Schlotheim), Corbicula sp. Valanginian age indicate a half - Hauterivian shallow marine environment and brackish waters close to shore. This same fossil fauna has been reported also in the areas of Cruz Blanca, Shaullo Chico y Huambocancha (Quadrangle Cajamarca). The fm. Carhuaz, also the name given by [1] of Cretaceous age, consists of alternating sandstones, siltstones and fine-grained strata commonly thin. In Matara Namora and has identified a fossil flora according to [3] are: Weichselia peruviana Zeiller (imprints of branches and leaves, Pelcurdia sp. indicating an age Valanginian - Hauterivian and a deposition in a continental environment and close to a transitional zone, with predominantly hot and humid climates. Applying the PMPR, methodology proposed by [4], the sandstones of the Fm. Sedimentology Carhuaz made in a column in the White Cross (Cajamarca) determined that the sandstones are located 46% of the top of the whole column, indicating that this location is close to the central part of the whole column. The area PMPR Namora (Quad San Marcos) is 55%. These results indicate that the facies located in Cajamarca are less continental those located in San Marcos. It seems that the rich content of organic matter, depositional character warm and salty waters of both bands have favored chemical reactions between hydrothermal fluids and such. Instead these chemical reactions occur equally well in a transgressive and regressive environmental nature within the formation Carhuáz.